Genome-wide analysis of the FAD gene family in Solanum tuberosum L. reveals its involvement in cold stress tolerance - Chu, Xiaoyue; Yuan, Baoqi; Li, Chuang; Qian, Xueyan; Yao, Yao; Qiao, Jianlei; Guo, Dongquan; Wang, Zhongwei (Frontiers in Plant Science, 2025)
Fatty acid desaturases (FADs) introduce double bonds into fatty acid chains, thereby maintaining membrane fluidity and modulating plant responses to stress. Yet the genome-wide features and functional implications of the FAD family in potato (Solanum tuberosum L.) remain insufficiently defined. Here, we identified 47 StFAD genes and analyzed their chromosomal distribution, phylogeny, conserved motifs, and promoter cis-elements. StFAD members were unevenly distributed across 12 chromosomes, with clusters on chromosomes 6 and 12, consistent with tandem and segmental duplications. Promoter analysis revealed abundant stress-, hormone-, and light-responsive elements, including cold-related motifs (LTR, ARE). Integrating transcriptome data with qRT–PCR, we found that StFAD7 was strongly and persistently induced by 4 °C treatment (12–24 h). This induction coincided with attenuation of MDA accumulation after 12 h, sustained increases in SOD and CAT activities, and a transient surge of POD activity at 12 h, linking StFAD7 expression to time-resolved physiological adjustments in tubers. Subcellular assays further showed that StFAD7–GFP localized predominantly to the plasma membrane, the first cellular interface challenged by low temperature, consistent with a role in lipid desaturation and redox homeostasis. These results support the hypothesis that StFAD7 may contribute to cold-induced lipid remodeling and oxidative stress alleviation in potato. Together, they refine the landscape of the potato FAD family and provide a rationale for functional studies and breeding strategies aimed at improving chilling tolerance.